Licorice ethanol extract improves symptoms of polycytic ovary syndrome in Letrozole-induced female rats - Hyun Yang; Hye Jin Kim; Bo-Jeong Pyun; Hye Won Lee (Integrative Medicine Research)
Background: Licorice (Glycyrrhizae radix et rhizome, GRR) has long been used as an ingredient in Korean traditional medicinal herbal formulas for various metabolic and reproductive diseases. Polycystic ovary syndrome (PCOS) is a common endocrine disorder in premenopausal women. In the present study, we examined the effects of GRR extract on PCOS-like symptoms in female rats. Methods: Symptoms of PCOS were induced by Letrozole treatment for 4 weeks in 6-week-old female SD rats, after which the effects of GRR extract on recovery of normal hormonal levels and polycystic ovaries were assessed. Serum levels of luteinizing hormone (LH), follicular-stimulating hormone (FSH), LH/FSH ratio, and follicular cysts were evaluated, followed by the expression levels of known follicular phase markers such as Kitl, Cyp11a1, and Ptgs2. Results: The serum level of FSH was reduced only in the Lestrozole treatment group (PCOS), whereas significant recovery of FSH level was observed in the Letrozole and GRR co-treatment group (PCOS + GRR). Serum LH levels were not altered in any of the groups. Furthermore, the LH/FSH ratio (known biomarker for PCOS) was elevated only in the Letrozole treatment group (PCOS), whereas it was significantly reduced in the Letrozole and GRR co-treatment group (PCOS + GRR). For histological changes, follicular cysts, antral follicles, and increased thickness of the theca- and granulosa layers were observed in the PCOS group, whereas these alterations were remarkably reversed by GRR treatment. Conclusion: These results suggest that GRR extract inhibits the symptoms of PCOS by regulating imbalanced hormonal levels and irregular ovarian follicles. Keywords: Glycyrrhizae radix et rhizoma, Letrozole, LH/FSH ratio, Licorice, Polycystic ovary syndrome